First-Line Chemo-Immunotherapy in SCLC: Outcomes of a Binational Real-World Study - Laura Moliner, MD; Núria Zellweger, MSc; Sabine Schmid, MD; Martina Bertschinger, MD; Christine Waibel, MD; Ferdinando Cerciello, MD, PhD; Patrizia Froesch, MD; Michael Mark, MD; Adrienne Bettini, MD; Pirmin Häuptle, MD; Veronika Blum, MD; Lisa Holer, MSc; et al. (JTO Clinical and Research Reports)
Introduction: SCLC is characterized by aggressiveness and limited treatment options, especially in extensive-stage SCLC (ES-SCLC). Immunotherapy added to the platinum-etoposide combination has recently become standard in this setting. This retrospective study aims to evaluate the real-world effectiveness of chemo-immunotherapy in patients with ES-SCLC, focusing on subpopulations excluded from clinical trials. Methods: A retrospective binational multicenter study was conducted, involving consecutive patients with ES-SCLC from 10 British and 10 Swiss institutions. Patients received platinum-etoposide chemotherapy in combination with immunotherapy (atezolizumab or durvalumab). Patient, tumor, and treatment details were collected. Overall survival (OS), progression-free survival, objective response rate, and safety outcomes were analyzed. Results: A total of 436 patients were included. One hundred forty-two patients (32.6%) in our cohort would not have been eligible for the pivotal registrational trials owing to an Eastern Cooperative Oncology Group performance status of 2 or higher, autoimmune disease, active brain metastases, or steroid use. Most patients received carboplatin (96.8%) and atezolizumab (97.9%). The median progression-free survival was 5.5 months and the median OS was 9.3 months. The two-year OS was 14%. Patients with liver or bone metastases or an Eastern Cooperative Oncology Group performance status of 2 or higher had worse survival outcomes. Treatment-related adverse events were reported in 222 patients (51%) whereas immune-related adverse events occurred in 95 patients (22%). Three out of five grade 5 immune-related adverse events were caused by pneumonitis. Conclusions: To our knowledge, this is the largest real-world cohort of patients treated with chemo-immunotherapy for ES-SCLC. Although one-third of patients would not have been eligible for pivotal trials, the survival outcomes in our cohort are similar to those in registrational trials. In particular, the number of long-term survivors and the safety data are comparable, supporting the use of chemo-immunotherapy as first-line treatment for ES-SCLC in daily clinical practice.